Application of phosphatidic acid in sport: reality or myth? - N. D. Golberg; V. А. Rogozkin (National Electronic Information Consortium (NEICON), 2020)
The mTOR enzyme plays an important role in the transmission of extracellular signals through the phosphorylation of numerous substrates in various metabolic reactions of the human body. Expression of mTOR occurs in response to changes in metabolic demands of the muscle cell and leads to increased protein metabolism. Among the substances that increase the catalytic activity of mTOR one of the main places is occupied by phosphatidic acid, the content of which in skeletal muscles increases when performing physical exertion. Studies of recent years indicate the important role of phosphatidic acid in increasing the intensity of the synthesis of muscle proteins. So, there is the need to consider the current state of knowledge about the involvement of phosphatidic acid in the regulation of skeletal muscle metabolism. The review presents the results of studies published over the last few years, which expand the understanding of the effects of phosphatidic acid in the human body.